PENGARUH MEDIA E-KOMIK TERHADAP MOTIVASI DAN HASIL BELAJAR PENDIDIKAN PANCASILA PESERTA DIDIK KELAS 5A DI SD INPRES BTN IKIP I - Nurul Aulia Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effect of using e-comic media on learning motivation and learning outcomes in Pancasila Education for grade 5A students at SD Inpres BTN IKIP I. The research employed a quantitative approach with a one-group pretest-posttest design. A total of 27 students were selected through purposive sampling. The instruments included a motivation questionnaire based on McClelland's theory and learning outcome tests guided by Bloom's Taxonomy. Data analysis involved Wilcoxon Signed Rank Test, paired sample t-test, and Pearson correlation using SPSS 30.0. Results indicated that the e-comic media significantly increased students' learning motivation and positively impacted their academic achievement. The average learning outcome increased from 42.92 to 81.85 with an N-Gain of 0.66 (moderate-high category), and a strong positive correlation (r = 0.892) was found between motivation and learning outcomes. This suggests that e- comics are an effective digital learning tool to improve both motivation and learning results in primary school civic education.